Exergetic and exergoeconomic analysis of a renewable polygeneration system and viability study for small isolated communities. (1st December 2015) - Calise, F.; Dentice d'Accadia, M.; Piacentino, A.
Abstract: A great interest has recently arisen for the sustainable supply of energy and fresh water, due to the growing demand from developing countries. Facing this demand by traditional technologies implies evident risks related with the high cost of fossil fuels and their environmental impact. Then, alternative solutions based on the use of renewable sources and innovative technologies must be considered. In this paper a renewable polygeneration system is examined, which includes a solar field based on parabolic trough photovoltaic/thermal collectors, a biomass heater, an absorption chiller and a Multiple Effect Distillation desalination unit. Plant operation under dynamic conditions has been analysed in previous papers; in this paper an exergetic and exergoeconomic analysis is carried out. The exergetic analysis is intended to identify the steps that mostly affect the overall plant exergy efficiency, so as to propose possible improvements. The exergoeconomic cost accounting is aimed at assigning a monetary value to each energy or material flow, thus providing a rational basis for price assignment. Both the exergetic and exergoeconomic analyses are applied to integral values of energy flows, comparing the results obtained in the summer and winter season. Finally, economic viability of the system in different context scenarios is discussed. Highlights: A renewable polygeneration system based on integrated CPVT-MED scheme is presented. Exergy and exergoeconomic analyses are performed, on seasonal and weekly bases. Exergoeconomic costs are assumed a reasonable basis for price assignment. The solar field is the main source of irreversibility. The system is economically viable only for disadvantaged areas.